2(x-9)+12=19

Simple and best practice solution for 2(x-9)+12=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-9)+12=19 equation:


Simplifying
2(x + -9) + 12 = 19

Reorder the terms:
2(-9 + x) + 12 = 19
(-9 * 2 + x * 2) + 12 = 19
(-18 + 2x) + 12 = 19

Reorder the terms:
-18 + 12 + 2x = 19

Combine like terms: -18 + 12 = -6
-6 + 2x = 19

Solving
-6 + 2x = 19

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 2x = 19 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 19 + 6
2x = 19 + 6

Combine like terms: 19 + 6 = 25
2x = 25

Divide each side by '2'.
x = 12.5

Simplifying
x = 12.5

See similar equations:

| 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 | | -20z-0.6=30z+1.3 | | 7(100+10)= | | w-38-34=-21 | | c-6=-9 | | 17x-7=2-x | | 9x-77=2x | | 3(50+25)= | | 19y=76 | | 4.87=m+0.87 | | 3(x-6)=9(x-2) | | 6-4(1-2x)=-23+3x | | 23+x=33 | | -2y^2+3y=-14 | | 6.4x=0.64 | | p+.03p=154.5 | | x-3.4=3.6 | | 63=-15+x | | 6.4x=.064 | | 6-x=4-.5x | | 2x^3+16y^3=0 | | 2x-11=83 | | 63=-15+4 | | x/2-9=-5 | | 8m-5=3 | | Y-9=42 |

Equations solver categories